Multi-agent system for stock traders - Korczak, Jerzy; Bac, Maciej; Drelczuk, Krzysztof; Fafuła, Aleksander (Wieloagentowy system dla graczy giełdowych, 2012)
The authors of this paper present the architecture of a multi-agent system which supports investment decisions on the stock market. The individual components of the system, the manner of communication between them and the mechanism of assessing the individual agents are discussed. New methods of pre-processing financial series, the concept of never- -ending learning, the behavioral model of stock exchange traders and the manners of translating the modeled patterns into the open and close position signals are described. The results of the research are described and the directions of the further development of the platform are provided in the conclusion
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 97-108
Keywords: multi-agent decision support systems; financial markets; stock trading expertise; artificial intelligence; time series analysis; system wieloagentowy; rynki finansowe; systemy doradcze na giełdzie; sztuczna inteligencja; analiza szeregów czasowych